Development of Company’s Creditworthiness Analysis Model Based on the Characteristics of the National Market - Ilić, Miloš; Saković, Dušan; Stanišić, Mile (Industrija, 2019)
The main issue for all creditors in the Republic of Serbia is how to effectively lend to companies, with adequate increase of rate of return. Namely, domestic creditors are using traditional credit analysis methods, which are very slow and very expensive, or on the other hand using one of the world most developed models for assessing company’s creditworthiness, which are still not adapted to the characteristics and performance of domestic companies. It is emphasized from a professional and practical standpoint, that the models for assessing company’s creditworthiness developed for individual market, give significantly better results than other “standardized models“, and this represents the basic assumption of this research. Financial statements of domestic companies, together with their analytical indicators, in best way reflect their characteristics. As such, they are the basis for developing a model for assessing companies’ creditworthiness, which is the main goal of the research. The hypothesis of the paper is “Respecting the characteristics of domestic companies, it is possible to develop a creditworthiness analysis model for the Republic of Serbia, that will be more efficient than generally known models”. The result of the research is a model that can be practically applied, which contributes to increasing efficiency in decision making, and which should represent “condition sine qua non” of each lender in Serbia.